Perbedaan tingkat stres primigravida yang bekerja dengan yang tidak bekerja di kecamatan jakenan kabupaten pati - Santoso, Heru Fery; , Prof. Dr. M. Fanani, dr, SpKJ (K); , Dr. Erna Herawati, Sp.K.J (2014)
BACKGROUND: The first pregnancy becomes the risk in pregnancy because it is the transition process of becoming mother. Psychological factor in facing childbirth is a very affecting factor of childbirth process. Woman has the second role which is as a working woman. She has to divide her time to work and rest for the health of fetus. A wife has very important roles which are to taking care her husband, household and her fetus in her womb. A housewife has no regular work time, it means that her job starts from she wake up until go back to sleep. PURPOSE: To understand the difference of primigravida stress level between working and non-working in Jakenan Sub-district of Pati Regency. METHOD: The type of this research is observational analysis design with cross sectional approach. The sampling technique in this research is conducted using quota sampling. The amount of this research is 82 consists of 41 working primigravida and non-working primigravida. The instrument research used in this research is application form, consent form, respondentsal data questionnaire, Lie Minnesota Multiphasic Respondentsality Inventory questionnaire (LMMPI), dan Depression Anxiety Stress Scale (DASS). RESULT: From working Primigravida, it is acquired 27 (65.9%) respondents with normal stress level and 14 (34.1%) respondents with beyond normal stress level. On the respondent of non-working primigravida category it is acquired 12 (29.3%) respondents with normal stress level and 29 (70.7%) respondents with beyond normal stress level. After data analysis is conducted by using Chi Square it is obtained value of p=0,001 (p<0,05), so it can be stated that there is a difference of stress level toward working and non-working primigravida. CONCLUSION: It can be concluded that there is a significant of stress level difference toward working and non-working primigravida in Jakenan sub-district of Pati regency and non-working primigravida has higher stress level rather than working primigravida.